4 Levels of IoT Architecture for Smart Irrigation Rice Fields - Hardyanto, R Hafid; Ciptadi, Prahenusa Wahyu; Setiawan, Endri (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2025)
Water is one of the main components in the agricultural sector. Traditional irrigation systems are often inefficient and ineffective, which can lead to water wastage and require huge resources. Intelligent irrigation systems based on the Internet of Things (IoT) offer a solution to overcome these problems. The purpose of this research is to create a 4 Layer IoT architecture for smart irrigation in Gadon village. The method used in this research uses research and development methods, starting from literature study, field survey, design, assembly, and testing. Design of Internet of Things (IoT) architecture using ESP8266 for irrigation of rice fields in Gadon village Dlingo, Bantul. The design of this system aims to facilitate irrigation. This system utilizes IoT technology in its implementation. This system consists of four IoT layers, namely the Smart Things layer which consists of a water level sensor, water ph sensor, with control using ESP8266. Networks and Gateways layer, which consists of a router to connect smart things with the internet, Middleware layer, and Application layer which consists of an android application for the system interface. This system contributes directly to the form of convenience for farmers to manage irrigation of rice fields using ESP8266-based IoT applications. In addition, this system also provides water level information to facilitate farmers in the irrigation process.